Предмет: Алгебра, автор: Аноним

дам 20 баллов пж помогите.​

Приложения:

Ответы

Автор ответа: RewMath
1

1) \frac{a^{2} -a -56}{a-8} =\frac{a^{2} -a-7a+7a -56}{a-8} =\frac{(a^{2} -8a)+(7a -56)}{a-8}=\frac{a(a -8)+7(a -8)}{a-8}= \frac{(a -8)(a +7)}{a-8}=a+7 \\

2) \frac{a^{2} + 6a - 27  }{a+9} = \frac{(a-a1)*(a-a2)}{a+9}

D = 6²-4*(-27)*1 = 36+108 = 144

a1=\frac{-6+\sqrt{144} }{2} =\frac{-6+12}{2} =\frac{6}{2}=3\\ a2=\frac{-6-\sqrt{144} }{2} =\frac{-6-12}{2} =\frac{-18}{2}=-9\\

\frac{(a-3)(a+9)}{a+9} =a-3

Похожие вопросы